Peran Layanan Terhadap Kepuasan Pelanggan Pada Sektor Perbankan - Derudebu Talunohi; Erlinda Sholihah (Lembaga Pengembangan Kinerja Dosen, 2023)
One type of competence that is crucial that must be managed by the banking industry is service. Future challenges will be increasingly severe and increasingly rapid technological advances require the banking sector to provide the best services in order to be able to compete in an increasingly tight business environment. The purpose of this study is to explore the factors that influence customer satisfaction in the banking industry in Indonesia. This research focuses on evaluating service quality, customer loyalty and security in improving customer satisfaction. This research is an empirical research built with primary data by distributing a questionnaire survey and getting 204 bank customers involved in the research. Furthermore, the data was processed using the SPSS program version 25 through validity and reliability testing. The findings showed that all variables studied affected customer satisfaction in the banking sector in Central Java. This research produced findings that show there is a positive and significant influence between service quality and customer loyalty to customer satisfaction; The findings also showed a negative correlation between security and customer satisfaction. The findings in this study provide additional new insights into studies related to service quality assessment in the banking sector in Central Java and Indonesia.